Temperature and doping-level dependence of magnetic order in La2-xSrxNiO4+delta studied by muon spin rotation - Jestadt, T; Chow, K; Blundell, S; Hayes, W; Pratt, F; Lovett, B; Green, M; Millburn, J; Rosseinsky, M (1999)
We report muon-spin-rotation (μSR) measurements on a series of compounds with composition La2-xSrxNiO4+δ with strontium doping level x between 0 and 1. A magnetic transition is found in all the samples studied, which occurs at a composition-dependent temperature, TM. Below TM clear precession signals are observed in zero applied magnetic field for all x, indicating the existence of at least short-range magnetic order on a time scale longer than 10-8 s. Above TM the magnetic correlation times decrease by several orders of magnitude. At x≈0.33, we find peaks in both TM and the zero-temperature staggered magnetization, an observation which we attribute to the higher degree of localization of the holes at this doping level. The measurements of TM as a function of x extend the determination of Néel temperatures by previous neutron diffraction and μSR measurements. © 1999 The American Physical Society.